Pelatihan Kewirausahaan Berbasis Potensi Lokal Untuk Meningkatkan Ekonomi Kreatif Masyarakat Desa: Penelitian - Umi Rahmawati; Annisa Nugraheni Afridhianika; Purwaka Hari Prihanto; Mulyadi; Rudy Irwansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This local potential-based entrepreneurship training aims to improve the creative economy of rural communities. The program's implementation includes preparation, identification of local potential, participant recruitment, training, mentoring, networking and marketing, and evaluation and monitoring. The results demonstrate that local potential-based entrepreneurship training has proven effective in increasing the knowledge, skills, and entrepreneurial attitudes of rural communities. Furthermore, the training successfully created high-value superior products, enhanced participants' digital marketing skills, expanded market access, and encouraged the formation of Joint Business Groups (KUB) as a platform for economic collaboration. Overall, this program significantly contributes to strengthening the village creative economy through innovation, digitalization, and a spirit of community mutual cooperation.